2016
DOI: 10.7566/jpsj.85.114713
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structures of Ferromagnetic CeAgSb2: Soft X-ray Absorption, Magnetic Circular Dichroism, and Angle-Resolved Photoemission Spectroscopies

Abstract: We report a combined study for the electronic structures of ferromagnetic CeAgSb2 using soft X-ray absorption (XAS), magnetic circular dichroism (XMCD), and angle-resolved photoemission (ARPES) spectroscopies. The Ce M4,5 XAS spectra show very small satellite structures, reflecting a strongly localized character of the Ce 4f electrons. The linear dichroism effects in the Ce M4,5 XAS spectra demonstrate the ground state Ce 4f symmetry of Γ6, the spatial distribution of which is directed along the c-axis. The XM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The lack of microscopic experimental information makes it difficult to reveal the origin of the quantum criticality for realistic HF systems, which is proposed on the basis of several models due to the spin fluctuation [25], Kondo breakdown [26][27][28], and valence fluctuation theories [29,30]. The HF phenomena are complicated by the strong momentum dependence of a HF nature arising from anisotropic cf hybridizations, which reflect the 4f charge distributions as clearly revealed by soft x-ray absorption spectroscopy [31][32][33]. To tackle this problem, it is essential to seriously investigate the band structures along various directions in three-dimensional (3D) reciprocal space.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of microscopic experimental information makes it difficult to reveal the origin of the quantum criticality for realistic HF systems, which is proposed on the basis of several models due to the spin fluctuation [25], Kondo breakdown [26][27][28], and valence fluctuation theories [29,30]. The HF phenomena are complicated by the strong momentum dependence of a HF nature arising from anisotropic cf hybridizations, which reflect the 4f charge distributions as clearly revealed by soft x-ray absorption spectroscopy [31][32][33]. To tackle this problem, it is essential to seriously investigate the band structures along various directions in three-dimensional (3D) reciprocal space.…”
Section: Introductionmentioning
confidence: 99%
“…The Sommerfeld coefficient of γ is 46 mJ/(mol•K 2 ), which gives the moderate mass enhancement factor of 21 for LaAgSb 2 [4]. The soft X-ray angle resolved photoemission experiments reported that the Ce 4 f states were almost localized and the experimental band structures are well explained by the band structure calculation for LaAgSb 2 [5], suggesting that the electronic structure is basically described as Ce 3+ ionic picture.…”
Section: Introductionmentioning
confidence: 87%
“…The anisotropy parameter α 2 along the c-axis of the Γ 7 states can be determined by linearly polarized X-ray absorption spectroscopy (XAS) [5][6][7][8]. However, it is insensitive for the in-plane rotational symmetry, which is described by the ± sign of the linear combination of the |± 5 2 ⟩ and |± 3 2 ⟩ states, due to the fundamental limitation of the dipole selection rule in the tetragonal systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations